A Corpus Study of the English Suffixes -ness and -acy: Productivity, Genre, and Implications for L2 Learning - Naismith, Ben; Kanwit, Matthew (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2021)
Despite substantial scholarship relating to word structure (Anderson, 2018), for English affixes the relationship between productivity, genre, and second language (L2) learning remains unclear. Analysis of the existing literature reveals that deadjectival noun suffixes (i.e., nouns derived from adjectives such as appropriacy or goodness) have been underexamined. To address this gap, we examine two rival suffixes, -acy and -ness, through the lens of Construction Morphology (Booij, 2010), considering numerous factors which might condition their varying usage. Critically, corpus data in the Corpus of Contemporary American English and the British National Corpus (Davies, 2008-) reveal the importance of considering these affixes’ productivity in relation to genre, since -acy is especially frequent in academic texts, principally within certain social sciences. The implications for learners and teachers of English as a second language are discussed, particularly higher-level learners building communicative competence in academic contexts, along with a preliminary learner corpus comparison of the two variants.